Biotin anchored nanostructured lipid carriers for targeted delivery of doxorubicin in management of mammary gland carcinoma through regulation of apoptotic modulator. (2nd January 2020) - Tripathi, Chandra B.; Parashar, Poonam; Arya, Malti; Singh, Mahendra; Kanoujia, Jovita; Kaithwas, Gaurav; Saraf, Shubhini A.
Abstract: Mammary gland tumour has the highest incidence rate and mortality in women, worldwide. The present study envisaged a molecularly targeted nanostructured lipid carrier (NLCs) for doxorubicin (Dox) delivery capable of inducing cellular apoptosis in mammary gland tumour. NLCs were prepared utilizing Perilla frutescens oil (54–69% ω3-fatty acid) as liquid lipid to enhance entrapment of Dox through molecular ion pairing. Biotin decorated NLCs (b-Dox-NLCs) were evaluated in vitro and in vivo . The b-Dox-NLCs showed particle size of 105.2 ± 3.5 nm, zeta potential −35 ± 2 mV, entrapment 99.15 ± 1.71%, drug content 19.67 ± 2.6 mg.g −1, biotin content 5.85 ± 0.64 µg.g −1 and drug release 98.67 ± 2.43% (facilitated by acidic microenvironment) respectively. MTT assay and Flow cytometric analysis revealed higher anti-proliferative capability of b-Dox-NLCs to force apoptosis in MCF-7 cell line vis-à-vis marketed Dox, evidenced by reactive oxygen species level and mitochondrial membrane potential mediated apoptosis. Enhanced antitumor targeting, therapeutic safety and efficacy was exhibited by b-Dox-NLCs, as investigated through tumour volume, animal survival, weight variation, cardiotoxicity and biodistribution studies in 7, 12-Dimethylbenz[a]anthracene induced mammary gland tumour. Immunoblotting assay demonstrated b-Dox-NLCs downregulated anti-apoptotic proteins, i.e. bcl-2, MMP-9 while upregulated pro-apoptotic proteins, i.e. caspase-9, p16 and BAX. The experimental results suggest that biotinylated ω3-fatty acid augmented NLCs loaded with Dox are capable of inducing programmed cell death in mammary tumour and can be utilized as safe and effective delivery system with enhanced potential for mammary gland carcinoma therapy.